Analisis Penerapan Pembelajaran Berdiferensiasi dengan Model Problem Based Learning Pada Mata Pelajaran Matematika Kelas V SDN Pandean Lamper 04 - Sugiarti, Sugiarti; Patonah, Siti; Ismartiningsih, Ismartiningsih (LPPM Institut Pendidikan Nusantara Global, 2024)
Education is a conscious effort in creating a learning environment and a pleasant process so that students actively develop their potential. Differentiated learning is one of the strategies that teachers can use to meet the needs of each student. Mathematics learning activities for some students are scary lessons, because they are not in accordance with their wishes. One way to make students active in learning Mathematics is to have a problem-solving-based learning model, so that learning is not only centered on teachers and students can solve problems related to mathematics. The purpose of this study is to determine the application of differentiated learning with the Problem Based Learning (PBL) model in Mathematics learning in grade V SDN Pandeanlamper 04 on measuring and comparing angles. The subjects of this study are 26 students. The research method used is qualitative descriptive. Data were obtained from classroom observations during learning and documentation results. Based on the results of the study, it was shown that teachers used differentiated content and processes in the implementation of differentiated learning. The grouping of students based on learning styles is visual, auditory, and kinesthetic. The application of the PBL model is used so that students can solve problems related to mathematical problems, especially in the material of measuring and comparing angles.